Association between acute ischemic stroke etiology and macroscopic aspect of retrieved clots: is a clot's color a warning light for underlying pathologies?. (3rd May 2019) - Sgreccia, Alessandro; Duchmann, Zoé; Desilles, Jean Philippe; Lapergue, Bertrand; Labreuche, Julien; Kyheng, Maeva; Bourcier, Romain; Consoli, Arturo
Abstract : Background: Few case reports have considered the chromatic aspect of retrieved clots and the possible association with their underlying etiology. Objective: The aim of our study was to analyze the frequency of the TOAST ischemic stroke typical (atrial fibrillation, dissection, atheroma) and atypical (infective endocarditis, cancer-related, valve-related thrombi) etiologies depending on the chromatic aspect of retrieved clots. Methods: A total of 255 anonymized and standardized clot photos of consecutive patients treated by mechanical thrombectomy for acute ischemic stroke were included. A double-blind evaluation was performed by two senior interventional neuroradiologists, who classified the visual aspects of the clots into two main patterns: red/black or white. Main patient characteristics, distribution of underlying stroke etiologies, and outcomes were compared between the two study groups. Results: The inter-reader agreement for clot colors was excellent (k=0.78). Two hundred and thirty-three patients were classified as having red/black clots and 22 as having white clots. A statistically significant association (p=0.001) between atypical etiologies and white clots was observed. Conclusions: White clots were significantly associated with atypical etiologies in this cohort, in particular, with infectious endocarditis.